2021
DOI: 10.1039/d1na00597a
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional self-assembled peptide nanoparticles for multimodal imaging-guided enhanced theranostic applications against glioblastoma multiforme

Abstract: This study describes the development of self-assembled peptide nanoparticles with improved functionality via modifications by using multimodal imaging tools and enhanced the therapeutic efficacy against brain tumor glioblastoma multiforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Additionally, the fluorescent/radioactive imaging properties of our novel-designed PDC were introduced in two-step reactions . First, the ε-amino group of the terminal lysine residue was covalently conjugated with carbonyl carbon of the near-infrared fluorescent (NIRF) dye cyanine 5.5 N -hydroxysuccinimide (NHS) ester to induce optical molecular imaging properties of PDC (Scheme , step 1) with a chemical purity of >95% as shown by UHPLC analysis ( R t = 8.360 min), while HR-MS analysis shows [M + H] + m / z : 2271.1069 a.m.u.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the fluorescent/radioactive imaging properties of our novel-designed PDC were introduced in two-step reactions . First, the ε-amino group of the terminal lysine residue was covalently conjugated with carbonyl carbon of the near-infrared fluorescent (NIRF) dye cyanine 5.5 N -hydroxysuccinimide (NHS) ester to induce optical molecular imaging properties of PDC (Scheme , step 1) with a chemical purity of >95% as shown by UHPLC analysis ( R t = 8.360 min), while HR-MS analysis shows [M + H] + m / z : 2271.1069 a.m.u.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the fluorescent/radioactive imaging properties of our novel-designed PDC were introduced in two-step reactions. 35 First, the ε-amino group of the terminal lysine residue was covalently conjugated with carbonyl carbon of the near-infrared fluorescent (NIRF) dye cyanine 5.5 N-hydroxysuccinimide (NHS) ester to induce optical molecular imaging properties of PDC (Scheme 2, step 1) with a chemical purity of >95% as shown by UHPLC analysis (R t = 8.360 min), while HR-MS analysis shows [M + H] + m/z: 2271.1069 a.m.u. In contrast, in the second reaction, the same ε-amino group of the terminal lysine residue was covalently conjugated with the deprotected β-carboxylic acid group of diethylenetriamine pentaacetic acid (DTPA) as a bifunctional chelating agent (BFCA) with a chemical purity of >97% (R t = 6.978 min), while HR-MS analysis shows [M + H] + m/z: 2079.2003 a.m.u.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Interestingly, these SAPNs showed high affinity and cytotoxicity for α v β 3 -integrin overexpressed on glioblastoma (U87MG) cells with EC 50 = 20 μM/L, as well as enhanced apoptosis rate (≥80% at 24 h incubation), and multimodal (SPECT/Optical) diagnostic functionality. 151 Furthermore, the same group synthesized a novel radiotracer ( 99m Tc-DTPA-c[RGDKLAK]) and studied its efficacy to diagnose Alzheimer's disease preclinically. The results showed that radiotracer was highly accumulated in α v β 3integrin expressing brain region with decreased uptake in the liver and kidneys having target-to-nontarget ratio 28.47 ± 2.53 at 3 h postinjection.…”
Section: ■ Peptides For Drug Delivery Systemmentioning
confidence: 99%
“…Rizvi et al had developed a Cy5.5-conjugated self-assembled peptide nanoprobe Cy5.5@SAPD- 99m Tc based on a novel head-to-tail cyclic RGD-KLAK heptapeptide sequence. The effectiveness and efficacy of this probe for the diagnosis of glioblastoma multiforme had been proven in the tumor-bearing female Balb/c mice models guided by FI/SPECT imaging ( Rizvi et al, 2021 ).…”
Section: Bimodal Imaging Of Tumor Based On Near-infrared-i Fluorescencementioning
confidence: 99%